Estudo da etiologia das principais bactérias isoladas de mastite bovina em rebanhos leiteiros de propriedades rurais de Goiás - MARTINS, Juliana Dias (2012)
The bovine mastitis consists of an inflammation of the mammary gland, with acute to chronic evolution, which occurs when an infectious agent attacks the mammary gland. It is characterized by physical, chemical and sensory alterations of the milk, caused by microorganisms that invade the mammary gland and cause pathological changes in the glandular tissue. Mastitis can be classified according to the form of presentation as clinical or subclinical. Several symptoms are observed in the clinical form of the disease such as the secretion of milk with lumps, pus or watery aspect, and edemaciated stiff and febrile teats and udder. On the other hand, no symptoms can be observed in the mammary gland and milk in subclinical cases. Mastitis is a major cause of economic losses in dairy cattle farms, mainly due to reduced milk production, changes in the composition and increased somatic cell count (CCS). The objective of this study was to evaluate the prevalence of the main bacteria that cause (clinical and subclinical) bovine mastitis, and to check the sensitivity to various antimicrobial agents of clinical mastitis. The agents most frequently isolated from clinical mastitis were Streptococcus uberis and Staphylococcus aureus and the antibiogram demonstrated greater sensitivity and efficacy of the active principles linezolid, amikacin, gentamicin and imipenen regarding the isolated agents. In subclinical mastitis Streptococcus agalactiae, Streptococcus uberis and Staphylococcus sp. Were the agents most frequently identified and that determined the highest mean values of CCS. The average CCS of cows with subclinical mastitis was approximately 743 x 103 cs/mL. The study was conducted in eight dairy farms in the State of Goiás. The results were obtained by frequency analysis. In conclusion, that the results emphasize the importance of assessing the sensitivity profile of microorganisms that cause clinical mastitis in each herd studied allowing greater precision in medication prescription for future cases of clinical mastitis and for dry cow therapy. The use of other techniques such as real time PCR is also important for the detection of the main microorganisms causin subclinical mastitis, which can be indicated as a routine method, due to its specificity, providing a precise bacteriological diagnosis.